Prevalence and 5-year incidence rate of dyslipidemia and its association with other coronary artery disease risk factors in Iran: Results of the Kerman coronary artery disease risk factors study (Phase 2) - Hamid Najafipour (Wolters Kluwer Medknow Publications, 2021)
Background: Dyslipidemia (DL) is an important risk factor of coronary artery disease (CAD). We evaluated DL prevalence and its 5-year incidence rate in southeastern Iran, to assess the severity and growth rate of this CAD risk factor in the region. Materials and Methods: This study was a part of the Kerman CAD Risk Factors Study Phase 2 (2014–2018) among 9996 individuals aged 15–80 years, from whom 2820 individuals had also participated in Phase 1 (2009–2011). In mg/dl, cholesterol ≥240 and/or low-density lipoprotein cholesterol ≥160 and/or high-density lipoprotein cholesterol <40 for men and <50 for women and/or triglyceride >200 were defined as DL. Results: The lipid profile of 9911 persons was analyzed. Overall 19.6% had borderline cholesterol and 6.4% suffered from hypercholesterolemia. 56.6% of the population (62.5% of females vs. 48.5% of males) suffer from DL, from whom 73.4% were undiagnosed. Female gender, advanced age, obesity, hypertension, diabetes, anxiety, and depression predicted DL in the study population. The prevalence of DL was significantly lower in Phase 2 (56.6%) compared to Phase 1 (81.4%). The prevalence of undiagnosed DL (UDL) and diagnosed DL (DDL) was 40.7% and 16.2%, respectively. The 5-year incidence rate of DL was 2.58 persons/100 person-years (3.24 in females vs. 2.20 in males). Conclusion: Although there were promising signs of a reduction in DL and increase in DDL in the last 5 years, a high percentage of the population have DL yet, from whom mostly are undiagnosed. DL was significantly associated with other CAD risk factors. Therefore, the health-care management system should improve its strategies to reduce the health burden of DL.